APPLYING DEONTOLOGICAL PRINCIPLES IN EFL DIGITAL COMMUNICATION - Sapayeva Zulayho Sherzodovna, (TADQIQOTLAR, 2026)
Abstract This  article  examines  the  application  of  deontological  principles  in  digital communication within English as a Foreign Language (EFL) education. The study is based  on  a  qualitative  analysis  of  existing  academic  literature  related  to  digital communication, ethics, and language teaching. The findings reveal that deontological ethics, emphasizing moral duties such as honesty, respect, responsibility, and privacy, significantly contributes to the development of ethical digital communication culture among future teachers. The results indicate that integrating deontological principles enhances  learners’  engagement,  promotes  responsible  behavior,  and  strengthens professional competencies. The study concludes that deontological ethics serves as a strong  methodological  foundation  for  fostering  ethical  awareness  and  effective communication in digital EFL environments.